Global Best Algorithm Based Parameter Identification of Solar Cell Models - Turgut, Oguz Emrah (International Journal of Intelligent Systems and Applications in Engineering, 2017)
Effectivity of the solar energy systems is thoroughly dependent of successful modeling of the I-V characteristic curves. However, due to the lack of information about the precise model parameters those are profoundly involved in characterizing governing equations; an efficient design has not been accurately accomplished by researchers yet. This article proposes Global Best Algorithm (GBEST) in order to extract unknown parameters of solar cell models accurately. In order to test the performance of the proposed optimizer, nine different unconstrained optimization test functions are evaluated and their statistical results are compared with the recently developed metaheuristic algorithms. GBEST is applied on PV module, single and double diode models which are mathematically formulated as multi-dimensional and highly nonlinear in their nature.Â Â  Results reveal that GBEST is superior to the other methods in terms of solution accuracy and efficiency.